MOTIVATION AND DEMOTIVATION FOR THE STUDENTS OF SMPN 1 MAKALE IN JOINING ENGLISH CLUB - Rachel Rachel; Normalia Sirande; Michael Linggi (Jurnal Andi Djemma | Jurnal Pendidikan, 2020)
The objective of this research are 1) to find out the factors motivate the students of SMPN 1 Makale in joining English club, and 2) to find out factors demotivate the students of SMPN 1 Makale in joining English Club.This research used qualitative method. The participant of this research was the students of SMPN 1 Makale. The researchers used snowball sampling technique. The researchers took 54 students to interview as participants. The data of this research was collected by interview. The researchers used open ended interview. The obtained data were analyzed in three major phase namely reduction, data display, and conclusion. The result of the research shows revealed 1) some factors that motivate the students of SMPN 1 Makale in joining English club, they are collaboration, communication, creativity, and innovation, and 2) some factors demotivate the students are teacher attitude, lack of facilities, teaching concepts, students did not like learning English. Based on the result above, it can be concluded that the students of SMPN 1 Makale have some factors that motivate and demotivate them in joining English Club.